Betanidin pKa prediction using DFT methods - Rodriguez, Sergio A. (2020)
Betalains can be used in food, drugs, and cosmetic industries and have shown their bioactive potential. These properties are strongly influenced by pH and other physicochemical conditions. The pKa values for the polyprotic Betanidin (Bd) molecule are unknown, and they are crucial to elucidate the oxidation mechanism in which its pigment is involved. In the present study, the values of pKa for all protic groups of Bd were analyzed using five hybrid density functionals (B3LYP, B3PW91, ωB97XD, PBE0, and M06-2X), five basis sets (6-31+G(d), 6-31+G(d,p), 6-31++G(d,p), 6-311+G(d,p), and 6-311++G(d,p)) and the solvation model based on density (SMD) implicit solvation model. Moreover, one and three explicit water molecules were added to improve the solvation free energy values. Furthermore, the values of pKa of betanin, betalamic acid, and cyclo-dihydroxyphenylalanine (DOPA) were studied. Based on these analyses, we propose the acid-base behavior of Bd in water and develop new tools to understand their chemical reactivity.